ESTUDO BIBLIOMÉTRICO SOBRE ATIVIDADE MOTORA ADAPTADA NO FIEP BULLETIM (Fiep Bulletin - online, 2024)
Introduction: Adapted motor activity (AMA) is a field of knowledge that aims to promote the inclusion and quality of life of people with disabilities or special needs through body and sports practices adapted to their characteristics and potential.  Objective: to analyze the articles on adapted motor activity published in the FIEP Bulletin. Methods: A bibliometric analysis was carried out to measure the productivity of scientific activity, producing ordered quantitative results, following the development and advances in knowledge. Conclusion: The publication of articles on the subject remained low , but stable.